Aplikasi Jamur Antagonis Trichoderma viride Terhadap Pengurangan Intensitas Serangan Penyakit Hawar Daun Serta Hasil Tanaman Kentang - Purwantisari, Susiana (Prosiding KPSDA, 2015)
The objective of this research was to studi ability of Trichoderma sp. fungal antagonist on reduction leaf blight intensity disease and potato yield. The in vivo experiment was carried out at potato land area located at BALITSA in Cikole Sub District, Lembang District and Bandung Regency. Completely Randomized Design was used with six treatment and five replicates. The treatment tested consist of control (without pathogen fungal and antagonists fungus application too), control (with pathogen fungal application and without antagonist fungal application), chemical fungicide application, antagonist fungal application 2 weeks before planting, application 1 week after planting and both application 2 weeks before and 1 week after planting. Result of the research showed that application of antagonists fungal could decrease disease intensity and tended to improve crop potato yield. Research repeatment with more quantity pouring the antagonist was needed. These antagonist could be used as biological agents initials to control leaf blight disease.